Desenvolvendo a educação financeira com o currículo: uma experiência com estudantes da 3ª série do ensino médio - Navarro, Gabriela Ferreira Gonçalves (2023)
Financial education encompasses the acquisition of knowledge, skills, and attitudes that empower individuals to make informed decisions about the management of financial resources. This paper describes an experience conducted with third-year high school students, aiming to emphasize the relevance of financial education in their curriculum. The employed method included conducting explanatory lessons and interactive activities to introduce fundamental concepts. Throughout the educational process, students learned to distinguish between needs and wants, understanding the difference between financial priorities and consumer impulses. Additionally, they received guidance on creating personal and family budgets, as well as understanding the concepts of simple and compound interest. The practical application of these concepts was promoted through challenging activities in which students solved real-world problems. The experience of incorporating financial education into the daily routine of high school students proved to be effective, not only increasing financial awareness but also empowering students to confidently and discerningly face the financial challenges they will encounter in their future. This reinforces the ongoing importance of financial education as a crucial tool for financial success and individual economic well-being.